The emotions of the Ancient Greeks : studies in Aristotle and classical literature - Konstan, David (Robson classical lectures., 2006)
"It is generally assumed that whatever else has changed about the human condition since the dawn of civilization, basic human emotions - love, fear, anger, envy, shame - have remained constant. David Konstan, however, argues that the emotions of the ancient Greeks were in some significant respects different from our own, and that recognizing these differences is important to understanding ancient Greek literature and culture."--Jacket